Sleep and Chronobiology as a Key to Understand Cluster Headache - Laura Pilati; Angelo Torrente; Paolo Alonge; Lavinia Vassallo; Simona Maccora; Andrea Gagliardo; Antonia Pignolo; Salvatore Iacono; Salvatore Ferlisi; Vincenzo Di Stefano; Cecilia Camarda; Filippo Brighina (MDPI AG, 2023)
The cluster headache is a primary headache characterized by attacks of unilateral pain associated with ipsilateral cranial autonomic features. These attacks recur in clusters during the years alternating with periods of complete remission, and their onset is often during the night. This annual and nocturnal periodicity hides a strong and mysterious link among CH, sleep, chronobiology and circadian rhythm. Behind this relationship, there may be the influence of genetic components or of anatomical structures such as the hypothalamus, which are both involved in regulating the biological clock and contributing even to the periodicity of cluster headaches. The bidirectional relationship manifests itself also with the presence of sleep disturbances in patients affected by cluster headaches. What if the key to studying the physiopathology of such disease could rely on the mechanisms of chronobiology? The purpose of this review is to analyze this link in order to interpret the pathophysiology of cluster headaches and the possible therapeutic implications.